Efecto del tiempo y temperatura de deshidratación en la calidad integral de un lomo de carne de cerdo - Anchundia Panta, José Andrés (2025)
This research aimed to evaluate the effect of drying time and temperature in an oven on the quality of pork loin. A completely randomized design (CRD) with a 3² bifactorial arrangement was used, considering three dehydration times (6, 7, and 8 hours) and three temperatures (65 °C, 70 °C, and 75 °C), resulting in nine treatments. Mechanical quality was evaluated through texture profile analysis (hardness, elasticity, fracturability, and resistance), nutritional quality (moisture, fat, ash, and protein), and microbiological quality (Staphylococcus aureus, Clostridium perfringens, and Salmonella sp.). A sensory acceptability test was also carried out, evaluating color, odor, flavor, and texture. The results showed that dehydration temperature (Factor B) influenced the mechanical and nutritional quality of the pork loin, while time (Factor A) did not show a significant effect (Sig. ≥ 0.05). At 75 °C (b3), the pork loin showed an increase in hardness, fracturability, and resistance, along with a decrease in elasticity and an increase in rigidity. Higher temperatures reduced moisture and fat content while increasing ash and protein levels. Microbiologically, treatments T6 (7 h + 75 °C) and T9 (8 h + 75 °C) complied with the RM591-MINSANORMA standard. Treatment T6 showed the highest acceptability in color, flavor, and texture, with no significant differences in odor.